Social policy for social work, social care and the caring professions : Scottish perspectives - Hothersall, Steve J.; Bolger, Janine (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This revised second edition analyses social policy in Scotland since devolution in 1999 and reflects the nascent and distinctively Scottish policy agenda. Along with updated chapters, there are two new inclusions: a chapter analysing post-devolution Scotland and a chapter on the likely impacts of Brexit on and within Scotland. Providing diagrams, tables and a range of activities, the book maintains an innovative and pedagogic emphasis to introduce students to a wealth of materials, ideas and practical responses to the increasingly complex and diverse situations faced by social workers and other professionals. Part one of the book looks at what social policy is, how and why it is made and highlights the importance of the relationship between social policy and the law. The second part refers to specific themes of social exclusion, poverty and (more visible for this revised edition) austerity, considering their complex and multidimensional forms and discussing the range of policies currently extant that aim to combat such disadvantage. Part three provides a comprehensive overview of policy for practice, considering concepts of health inequality, mental health, older people, disability, children and families, education, substance use, criminal justice, asylum and immigration and homelessness. This book will be of interest to undergraduate and postgraduate students as well as post-qualified professionals seeking to understand the complexities of the social policy landscape in Scotland, and its influence on social work and related forms of professional practice"--
Revised edition of Social policy for social work, social care and the caring professions, c2010.
OCLC-licensed vendor bibliographic record.
Keywords: Public welfare -- Scotland; Social service -- Government policy -- Scotland; Scotland -- Social policy; POLITICAL SCIENCE / Public Policy / Social Policy; SOCIAL SCIENCE / Social Work